Amyloid-beta-derived peptidomimetics inhibits tau aggregation - Gorantla, V. Nalini; Sunny, Lisni P.; Rajasekhar, Kolla; Nagaraju, Pramod G.; Priyadarshini, Poornima C. G.; Govindaraju, Thimmaiah; Chinnathambi, Subashchandrabose (ACS Omega, 2021)
The aggregation of tau protein is one of the hallmarks for Alzheimer's disease, resulting in neurodegeneration. The peptidomimetics strategy to prevent tau aggregation is more specific over other small molecules. In the present study, we analyzed the effect of amyloid-beta-derived peptidomimetics for inhibiting heparin-induced tau aggregation in vitro. These peptides and their derivatives were known to prevent aggregation of amyloid-beta. KLVFF is a hydrophobic sequence of the pentapeptide that prevented tau aggregation as observed by thioflavin S fluorescence, transmission electron microscopy, and circular dichroism spectroscopy. P4 and P5 also prevented assembly of tau into aggregates and formed short fibrils. The beta-sheet breaker LPFFD was however ineffective in preventing tau aggregation. The peptides further demonstrated reversal of tau-induced cytotoxicity in a dose-dependent manner. Our results suggested that these peptides can also be used to inhibit tau aggregation and also, toxicity induced by tau could be considered as potential molecules that have an effect on tau as well as amyloid-beta.

Tryptophan-cardanol fluorescent nanoparticles inhibit alpha-synuclein aggregation and disrupt amyloid fibrils - Sunny, Lisni P.; Srikanth, Priya; Sunitha, Anju Kunhiraman; Tembulkar, Niyoti; Abraham, Jancy Nixon (Journal of Peptide Science, 2022)
Protein misfolding and aggregation play a vital role in several human diseases such as Parkinson's, Alzheimer's, and prion diseases. The development of nanoparticles that modulate aggregation could be potential drug candidates for these neurodegenerative disorders. Parkinson's disease pathogenesis is closely associated with the accumulation of alpha-synuclein oligomers and fibrils in the substantia nigra of the brain. This report discusses the interactions of novel tryptophan-cardanol nanoparticles with alpha-synuclein protein monomers and fibrils. These nanoparticles could effectively disrupt alpha-synuclein fibrils and inhibit fibril formation at low concentrations such as 5 mu M. The tryptophan-cardanol nanoparticles inhibit fibril formation from unstructured protein resulting in spherical nanostructures. These nanoparticles could also disassemble amyloid fibrils; the complete disappearance of fibrils was evident after 48 h of incubation with tryptophan-cardanol. The transmission electron microscopy (TEM) micrographs after the incubation did not show any remnants of the peptide aggregates or oligomers. The thioflavin T fluorescence after the disassembly was diminished compared with that of fibrils also supports the inhibitory effect of the nanoparticles. Also, these nanoparticles did not reduce the viability of the SH-SY5Y cells. These findings suggest that the tryptophan-cardanol nanoparticles showed sufficiently high inhibitory activity and may have therapeutic potential for synucleinopathies.
Keywords: alpha-synuclein; amyloid fibrils; Cardanol; inhibitors; Tryptophan